Dynamic reallocation rules on multi-server web-based MORPG system. (1st January 2012) - Kohana, Masaki; Okamoto, Shusuke; Kamada, Masaru; Yonekura, Tatsuhiro
The web-based-application user base has witnessed rapid growth. It has become necessary to develop techniques that enable systems to manage simultaneous access by a large number of users. We focus on web-based MultiPlayer Online Role-Playing Games (MORPGs), which must be able to cope with a large number of users and a high frequency of user requests. In our previous work, we introduced a system using multiple web servers and a dynamic data allocation method, which is able to manage dynamic change in user requests. Using this method, we achieved a capacity of 320 users, as opposed to the user capacity of 200 for single-server MORPG system. However, we found some cases in which our method was not effective. In this paper, we propose three rules for dynamic data allocation to address different situations. Our evaluation shows that the cache works effectively if the most avatars gather in a certain place.